NEGATIVE STIFFNESS HONEYCOMB STRUCTURE FOR OBJECT DETECTION/MANIPULATION AND CONTINUUM ROBOT SLIDING SYSTEM - Chibar, Rustam (School of Engineering and Digital Sciences, 2023)
In this work we tackle with problem using a negative stiffness honeycomb designed as a tactile sensor enabling to detect physical contact with low impact force. A lower impact force is achieved by varying the state of the honeycomb. At different states, the honeycomb behaves as a spring with both positive or negative stiffness coefficients. A tendon-driven mechanism controls the state of this honeycomb. The experimental results showed that the honeycomb attachment enabled the detection of a contact with a lower impact force. We also conducted experiments on soft and rigid objects, and demonstrated that the response of the system can be changed without altering the PID gains of the robot arm. This was achieved by controlling the state of the honeycomb, while keeping the controller the same. We also show that by rapidly changing the state of the such dexterous end-effector, the robot to punch an inverted pendulum. The results showed that the honeycomb attachment allowed for a more precise and controlled impact, resulting in improved stability of the pendulum. Moreover, we showed that negative stiffness honeycomb can be effective for decreasing weight and torque concentrated area in continuum robot segments. Our findings suggest that the honeycomb attachment can be a valuable tool for a range of applications, such as robotic manipulation, grasping and sensing, where low-impact and high-precision contact is required, as well as in continuum robot. Overall, our study highlights the potential of negative stiffness honeycomb structures as a means of improving the performance and versatility of robotic systems.
Keywords: type of access: restricted access; Negative Stiffness Honeycomb Structure; robot sliding system